2003
DOI: 10.1046/j.0905-6157.2003.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to food and airborne allergens in children with atopic dermatitis followed up to 7 years of age

Abstract: Previously we investigated the eczema prognosis and the risk of developing allergic asthma and rhinitis in a cohort of 94 children with atopic dermatitis. In this second study on the same cohort we address the development of sensitization to foods and airborne allergens, risk factors and, the question whether children with atopic dermatitis who will not become sensitized can be recognized early. Children with atopic dermatitis were followed up regularly from infancy or early childhood to 7 years of age with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 30 publications
7
26
1
3
Order By: Relevance
“…Remaining sensitization to egg at 4.5 years of age was associated with both ARC and asthma development, confirming several other studies [37], [42]. In early childhood, sensitization to hen's egg has been associated with sensitization to airborne allergens [43]. At the age of 10 we found no correlation for egg sensitization, ARC and asthma.…”
Section: Discussionsupporting
confidence: 89%
“…Remaining sensitization to egg at 4.5 years of age was associated with both ARC and asthma development, confirming several other studies [37], [42]. In early childhood, sensitization to hen's egg has been associated with sensitization to airborne allergens [43]. At the age of 10 we found no correlation for egg sensitization, ARC and asthma.…”
Section: Discussionsupporting
confidence: 89%
“…4,15 Sensitization to hen's egg is a strong predictor of later atopy 16,17 ; we showed that a positive SPT response with hen's egg at the time of diagnosis predicted the persistence of CMA. In addition, early exposure to CM was related to delayed development of tolerance to CM.…”
Section: Discussionmentioning
confidence: 90%
“…Children with atopic dermatitis were followed-up regularly from infancy to age 7 to look at the risk factors for sensitization to food and airborne allergens [76]. In this cohort, reactions to milk and eggs (as documented by positive skin tests) were transient but reactivity to peanuts was persistent.…”
Section: Atopic Dermatitismentioning
confidence: 99%